1989
DOI: 10.1177/088307388900400303
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Focal Periodic Discharges in Neonates

Abstract: Of 1,114 EEG recordings obtained for 592 neonates, focal periodic discharges were noted on 57 (5%) of recordings for 34 neonates (26 preterm and eight term). Periodic lateralized epileptiform discharges (PLEDs) were noted on four of these recordings. Sixteen patients (47%) with focal periodic discharges also had electrographic seizures on the same or a subsequent record. Stroke was the most common brain lesion (53%) in this neonatal population. Preterm neonates had discharges that were less than 60 seconds in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 40 publications
(19 reference statements)
0
13
0
Order By: Relevance
“…2, 1993 Although the EEG has been emphasized as the means by which seizures are diagnosed (Mizrahi and Kellaway, 1987;, Shewmon, 1990) emphasizes the problems in defining an electrographic seizure by surface-EEG recordings. Shewmon (1990) suggested that the arbitrary duration of 10 s does not allow consideration of brief intermittent rhythmic discharges (BIRDS) or prolonged periodic discharges as ictal phenomena (Scher and Beggarly, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2, 1993 Although the EEG has been emphasized as the means by which seizures are diagnosed (Mizrahi and Kellaway, 1987;, Shewmon, 1990) emphasizes the problems in defining an electrographic seizure by surface-EEG recordings. Shewmon (1990) suggested that the arbitrary duration of 10 s does not allow consideration of brief intermittent rhythmic discharges (BIRDS) or prolonged periodic discharges as ictal phenomena (Scher and Beggarly, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Average seizure duration was calculated based on averages for each of the three age groups of neonates. Brief, intermittent, rhythmic discharges (i.e., BIRDS) (Shewmon, 1990) or prolonged periodic discharges (Scher and Beggarly, 1989) were not included in this classification. Each EEG recording was visually analyzed by two of the authors (M.S.S.…”
Section: Eeg Seizure Definitionmentioning
confidence: 99%
“…The presence of asymmetrical EEG abnormalities has been associated with focal structural brain lesions such as stroke in children. 5,6,23,24,[43][44][45] However, asymmetrical EEG abnormalities with HIE 23,44 and transient asymmetries of the background in healthy term neonates 45,46 have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…A definitive causal link between the characteristics of the neonatal EEG and the subsequent neurological outcome is difficult to establish in humans. Thus it is unclear whether acute neonatal seizures are causes of, or merely symptoms of, other processes that lead to a negative outcome, making it difficult to gauge the necessity and efficacy of early clinical interventions to suppress seizures during the critical "subacute" period after neonatal insults (Monod et al 1972;Tharp et al 1981;Scher and Beggarly 1989;Williams et al 1992;Holmes and Lombroso 1993;Murray et al 2009;Korotchikova et al 2011;Walsh et al 2011). Furthermore, other events besides seizures, such as background abnormalities in the EEG, have been proposed to be better predictors of outcome (Monod et al 1972;Tharp et al 1981;Watanabe et al 1980Watanabe et al , 1982bHolmes and Lombroso 1993), but well-designed prospective studies on the neonatal EEG are limited.…”
mentioning
confidence: 99%